Trends in biomathematics : mathematical modeling for health, harvesting, and population dynamics : selected works presented at the BIOMAT Consortium Lectures, Morocco 2018 /: mathematical modeling for health, harvesting, and population dynamics : selected works presented at the BIOMAT Consortium Lectures, Morocco 2018. ([2019]) - Unknown
No abstract available